Los mensajes radiales en idioma Kichwa y el desarrollo de la interculturalidad en la Parroquia Zumbahua del cantón Pujili”, año 2021 - Chaluisa Chaluisa, Luis Diego (2021)
Indigenous communities and peoples perceive the real ambition to demonstrate their rights to collective communication. It's not just about showing your culture, your worldview, your needs and suggestions. There is talk of radio communication with the potential of being the only remedy to improve native cultures through its broadcasts and the possibility of inserting the Kichwa language in a timely manner and preventing its extinction from the radio media of the Zumbahua parish. The current research project aims to express the desire to establish points in which there is strong communication in the Kichwa-speaking groups or communities located in the Pujilí Canton; promptly, the people of the Zumbahua parish. The development of the research was constituted by Chapter I, it contains as its central axis a specialized methodological framework, where the topic or case study was defined, followed by an approach to the problem according to the needs of the research considering the importance of the Kichwa language, later, the reason for the importance of radio programs in the canton will be justified. Both general and specific objectives are of the utmost importance to achieve that the language is transmitted in the local communication media. The methodologist provided the necessary resources in terms of types and techniques of scientific research and the way in which information was collected and analyzed for its presentation, finally, it was possible to conclude and correctly recommend the investigation.